A power battery liquid cooling plate and a preparation method thereof
Patent Information
- Application Number
- CN202611263037.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-27
AI Technical Summary
随着新型低电导率冷却液的应用,由4/3系、3系铝合金板材经冲压、钎焊而成的普通液冷板在低电导率冷却液中的耐腐蚀性能已无法满足要求
(1) 本发明通过在液冷板上板和液冷板下板内侧分别复合一层包覆率为5%~15%的1xxx系改性铝合金或7xxx系改性铝合金,并优化合金成分(Ti+Zr微合金化、控制Si/Fe/Zn含量),通过Ti+Zr微合金化、成分优化(Si/Fe/Zn控制)和包覆率协同控制,在低电导率冷却液这一严苛环境中实现了多项协同增效,在保证液冷板力学性能的前提下,使液冷板在低电导率冷却液环境中的耐腐蚀性能得到大幅度提升,有效延长了液冷板在新国标GB/T29743.2电动汽车冷却液标准要求下的使用寿命。
Smart Images

Figure CN122992220A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of power battery thermal management technology, specifically relating to a power battery liquid cooling plate and its preparation method. Background Technology
[0002] By 2025, global sales of new energy vehicles will exceed 16 million units, with a market share of over 47.9%. As a core component of the power system of new energy vehicles, the power battery requires liquid cooling plates for heat management to ensure its safety.
[0003] To ensure the safety of electric vehicles and fundamentally reduce the risk of short circuits or even vehicle fires caused by coolant leaks, the new national standard for electric vehicle coolants (GB / T29743.2-2025) explicitly requires the use of coolants with lower conductivity, specifying a conductivity ≤100 μS / cm. However, low-conductivity coolants place higher demands on the corrosion resistance of liquid cooling plate materials: on the one hand, due to their low ion concentration, low-conductivity coolants exacerbate the electrochemical potential difference between the metal material and the coolant, increasing the tendency for electrochemical corrosion; on the other hand, the solubility of corrosion inhibitors in traditional coolants decreases in low-conductivity systems, weakening their corrosion inhibition effect and making liquid cooling plates more susceptible to localized corrosion.
[0004] Currently, most liquid cooling plates are made of aluminum alloy, typically formed by stamping and brazing 4 / 3 series or 3 series aluminum alloy sheets. With the application of new low-conductivity coolants, the corrosion resistance of ordinary liquid cooling plates made from 4 / 3 series or 3 series aluminum alloy sheets through stamping and brazing is no longer sufficient in low-conductivity coolants. Therefore, there is an urgent need to develop a liquid cooling plate for power batteries that combines excellent corrosion resistance and mechanical properties, and is compatible with low-conductivity coolants. Summary of the Invention
[0005] In view of this, the purpose of the present invention is to provide a power battery liquid cooling plate that has both excellent corrosion resistance and mechanical properties and is compatible with low conductivity coolant.
[0006] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a power battery liquid cooling plate, comprising an upper liquid cooling plate and a lower liquid cooling plate; the upper liquid cooling plate includes an upper substrate and an inner anti-corrosion layer, and the lower liquid cooling plate includes a lower brazing layer, an inner anti-corrosion layer, and a lower substrate; the upper and lower substrates are made of 3003 aluminum alloy or 3003 modified aluminum alloy, the brazing layer of the lower plate is made of 4045 aluminum alloy or 4343 aluminum alloy, and the inner anti-corrosion layers of the upper and lower plates are made of 1xxx series modified aluminum alloy or 7xxx series modified aluminum alloy.
[0007] Further, the mass percentage composition of the 1xxx series modified aluminum alloy is: Si≤0.5wt.%, Fe≤0.5wt.%, Cu≤0.1wt.%, Mn≤0.3wt.%, Mg≤0.3wt.%, Zn≤0.1wt.%, Ti: 0.05~0.2wt.%, Zr: 0.05~0.2wt.%, and the balance Al; the mass percentage composition of the 7xxx series modified aluminum alloy is: Si≤0.7wt.%, Fe≤0.8wt.%, Cu≤0.3wt.%, Mn≤0.3wt.%, Mg≤0.1wt.%, Zn: 0.5~2.0wt.%, Ti: 0.05~0.2wt.%, Zr: 0.05~0.2wt.%, and the balance Al.
[0008] Further, the 3003 aluminum alloy has the following mass percentage composition: Si ≤ 0.6 wt.%, Fe ≤ 0.7 wt.%, Cu: 0.05~0.20 wt.%, Mn: 1.0~1.5 wt.%, Zn ≤ 0.1 wt.%, and the balance Al; the 3003 modified aluminum alloy has the following mass percentage composition: Si: 0.1~1.0 wt.%, Fe: 0.1~1.0 wt.%, Cu: 0.2~1.2 wt.%, Mn: 1.0~1.8 wt.%, Mg ≤ 0.05 wt.%, Zn ≤ 0.1 wt.%, Ti: 0.05~0.30 wt.%, and the balance Al.
[0009] Further, the 4045 aluminum alloy has the following mass percentage composition: Si: 9-11 wt.%, Fe≤0.8 wt.%, Cu≤0.30 wt.%, Mn≤0.05 wt.%, Mg≤0.05 wt.%, Zn≤0.1 wt.%, Ti≤0.2 wt.%, and the balance Al; the 4343 aluminum alloy has the following mass percentage composition: Si: 6.8-8.2 wt.%, Fe≤0.8 wt.%, Cu≤0.25 wt.%, Mn≤0.1 wt.%, Zn≤0.2 wt.%, and the balance Al.
[0010] Furthermore, the coverage rate of the brazing layer on the lower plate is 5% to 15%.
[0011] Furthermore, the coverage rate of the anti-corrosion layer on the inner side of the upper plate and the anti-corrosion layer on the inner side of the lower plate is 5% to 15%.
[0012] The present invention also provides a method for preparing the above-mentioned liquid-cooled plate, comprising the following steps: S1: Melting: Melt aluminum liquid by melting according to the alloy composition ratios of the upper plate substrate and the upper plate inner anti-corrosion layer, the lower plate brazing layer, the lower plate inner anti-corrosion layer and the lower plate substrate respectively. S2: Casting: After the molten aluminum is passed through a converter, refined, settled, degassed and filtered, it is cast to obtain ingots of the upper plate substrate, the upper plate inner anti-corrosion layer, the lower plate brazing layer, the lower plate inner anti-corrosion layer and the lower plate substrate. Then, the ingots are sawed and milled. Among them, the ingots of the upper plate substrate and the lower plate substrate need to be homogenized before sawing and milling. S3: Composite hot rolling: After stacking and fixing the upper plate substrate and the upper plate inner anti-corrosion layer ingot, composite hot rolling is performed. After stacking and fixing the lower plate brazing layer, the lower plate inner anti-corrosion layer and the lower plate substrate ingot, composite hot rolling is performed to obtain the upper plate hot-rolled plate and the lower plate hot-rolled plate. S4: Cold rolling: The upper hot-rolled plate and the lower hot-rolled plate are cold-rolled and then annealed to obtain the upper liquid-cooled plate and the lower liquid-cooled plate. S5: Stamping: Stamping the lower plate of the liquid cooling plate to obtain flow channel grooves; S6: Brazing: The upper plate of the liquid cooling plate is brazed with the stamped lower plate of the liquid cooling plate under gas protection to obtain the liquid cooling plate.
[0013] Further, in step S1, the melting temperature is 700–750℃; in step S2, the homogenization treatment temperature is 520–590℃, and the time is 10–24 h; in step S3, the initial rolling temperature of the composite hot rolling is 400–480℃, and the thickness after rolling is 4–10 mm; in step S4, the annealing temperature is 240–320℃, the time is 1–4 h, and the thickness of the upper and lower liquid-cooled plates is 0.5–4 mm; in step S6, the brazing temperature is 590–620℃, the holding time is 3–10 min, and the protective gas is nitrogen.
[0014] The beneficial effects of this invention are as follows: (1) This invention combines a layer of 1xxx series modified aluminum alloy or 7xxx series modified aluminum alloy with a coating rate of 5% to 15% on the inner side of the upper and lower plates of the liquid cooling plate, and optimizes the alloy composition (Ti+Zr micro-alloying, control of Si / Fe / Zn content). Through Ti+Zr micro-alloying, composition optimization (Si / Fe / Zn control) and coating rate synergistic control, multiple synergistic effects are achieved in the harsh environment of low conductivity coolant. Under the premise of ensuring the mechanical properties of the liquid cooling plate, the corrosion resistance of the liquid cooling plate in the low conductivity coolant environment is greatly improved, and the service life of the liquid cooling plate is effectively extended under the requirements of the new national standard GB / T29743.2 electric vehicle coolant standard.
[0015] (2) The present invention adopts conventional rolling composite process, without the need for additional complex equipment or high-cost materials, and can be directly implemented on existing rolling composite production lines. It has low manufacturing cost and is suitable for large-scale industrial production.
[0016] (3) This invention significantly reduces the Zn content to 0.5-2.0% and adds Ti and Zr. Ti forms TiAl3 heterogeneous nucleation cores during the casting stage to refine the as-cast grains, and Zr inhibits recrystallization and grain growth during subsequent hot working and brazing. The two produce a time-space dual synergistic effect, achieving full grain refinement from casting to finished product. On this basis, Zr further enhances the thermal stability of the microstructure, so that the 7xxx series modified aluminum alloy does not overheat after brazing and maintains excellent corrosion resistance (40.2-47.2μm) and mechanical properties (158.9-166.5MPa). Attached Figure Description
[0017] Figure 1 This is a schematic diagram of the structure of the liquid cooling plate of the present invention; in the figure, 1: upper plate substrate, 2: inner anti-corrosion layer of upper plate, 3: lower plate brazing layer, 4: inner anti-corrosion layer of lower plate, 5: lower plate substrate.
[0018] Figure 2 This is a schematic diagram of the preparation method of the liquid cooling plate of the present invention.
[0019] Figure 3 This is a comparison diagram of corrosion depth between embodiments and comparative examples of the present invention. Detailed Implementation
[0020] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are only illustrative and explanatory of the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention. It should be noted that the experimental materials in the embodiments of the present invention whose source is not specified are all commercially available, and the experimental methods in the embodiments of the present invention whose specific conditions are not specified are generally carried out according to conventional experimental methods or according to the methods recommended by the experimental material manufacturers. It should be noted that the 1xxx series modified aluminum alloy described in the present invention refers to an aluminum alloy obtained by modifying it by adding a small amount of Ti, Zr and other elements based on the microstructure characteristics of 1xxx series aluminum alloys (with α-Al solid solution as the matrix and no large amount of second phase). Its corrosion resistance mechanism is consistent with that of 1xxx series, mainly relying on the surface oxide film to provide barrier protection. The 7xxx series modified aluminum alloy described in this invention refers to an aluminum alloy obtained by significantly reducing the Zn content to 0.5–2.0 wt.% and adding elements such as Ti and Zr, based on the corrosion protection mechanism of 7xxx series aluminum alloys (relying on Zn to lower the potential and provide sacrificial anode protection). It is suitable for brazing processes while retaining the sacrificial anode protection mechanism. Unless otherwise stated, all numerical ranges in this invention include their endpoint values and any specific values between the endpoints.
[0021] like Figure 1As shown, the present invention provides a power battery liquid cooling plate, including an upper liquid cooling plate and a lower liquid cooling plate; the upper liquid cooling plate includes an upper substrate 1 and an inner anti-corrosion layer 2, and the lower liquid cooling plate includes a lower brazing layer 3, an inner anti-corrosion layer 4, and a lower substrate 5; the upper substrate 1 and the lower substrate 5 are made of 3003 aluminum alloy or 3003 modified aluminum alloy, the lower brazing layer 3 is made of 4045 aluminum alloy or 4343 aluminum alloy, and the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate are made of 1xxx series modified aluminum alloy or 7xxx series modified aluminum alloy.
[0022] Further, the mass percentage composition of the 1xxx series modified aluminum alloy is: Si≤0.5wt.%, Fe≤0.5wt.%, Cu≤0.1wt.%, Mn≤0.3wt.%, Mg≤0.3wt.%, Zn≤0.1wt.%, Ti: 0.05~0.2wt.%, Zr: 0.05~0.2wt.%, and the balance Al; the mass percentage composition of the 7xxx series modified aluminum alloy is: Si≤0.7wt.%, Fe≤0.8wt.%, Cu≤0.3wt.%, Mn≤0.3wt.%, Mg≤0.1wt.%, Zn: 0.5~2.0wt.%, Ti: 0.05~0.2wt.%, Zr: 0.05~0.2wt.%, and the balance Al.
[0023] Further, the 3003 aluminum alloy has the following mass percentage composition: Si ≤ 0.6 wt.%, Fe ≤ 0.7 wt.%, Cu: 0.05~0.20 wt.%, Mn: 1.0~1.5 wt.%, Zn ≤ 0.1 wt.%, and the balance Al; the 3003 modified aluminum alloy has the following mass percentage composition: Si: 0.1~1.0 wt.%, Fe: 0.1~1.0 wt.%, Cu: 0.2~1.2 wt.%, Mn: 1.0~1.8 wt.%, Mg ≤ 0.05 wt.%, Zn ≤ 0.1 wt.%, Ti: 0.05~0.30 wt.%, and the balance Al.
[0024] Further, the 4045 aluminum alloy has the following mass percentage composition: Si: 9-11 wt.%, Fe≤0.8 wt.%, Cu≤0.30 wt.%, Mn≤0.05 wt.%, Mg≤0.05 wt.%, Zn≤0.1 wt.%, Ti≤0.2 wt.%, and the balance Al; the 4343 aluminum alloy has the following mass percentage composition: Si: 6.8-8.2 wt.%, Fe≤0.8 wt.%, Cu≤0.25 wt.%, Mn≤0.1 wt.%, Zn≤0.2 wt.%, and the balance Al.
[0025] Furthermore, the coverage rate of the brazing layer 3 on the lower plate is 5% to 15%.
[0026] Furthermore, the coverage rate of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate is 5% to 15%.
[0027] like Figure 2 As shown, the present invention also provides a method for preparing the above-mentioned liquid-cooled plate, comprising the following steps: S1: Melting: Melting is carried out according to the alloy composition ratios of the upper plate substrate 1 and the upper plate inner anti-corrosion layer 2, the lower plate brazing layer 3, the lower plate inner anti-corrosion layer 4 and the lower plate substrate 5 respectively to obtain aluminum liquid. S2: Casting: After the molten aluminum is passed through a converter, refined, settled, degassed and filtered, it is cast to obtain ingots of upper plate substrate 1, upper plate inner anti-corrosion layer 2, lower plate brazing layer 3, lower plate inner anti-corrosion layer 4 and lower plate substrate 5. Then, the ingots are sawed and milled. Among them, the ingots of upper plate substrate 1 and lower plate substrate 5 need to be homogenized before sawing and milling. S3: Composite hot rolling: After stacking and fixing the upper plate substrate 1 and the upper plate inner anti-corrosion layer 2 ingot, composite hot rolling is performed. After stacking and fixing the lower plate brazing layer 3, the lower plate inner anti-corrosion layer 4 and the lower plate substrate 5 ingot, composite hot rolling is performed to obtain the upper plate hot-rolled plate and the lower plate hot-rolled plate. S4: Cold rolling: The upper hot-rolled plate and the lower hot-rolled plate are cold-rolled and then annealed to obtain the upper liquid-cooled plate and the lower liquid-cooled plate. S5: Stamping: Stamping the lower plate of the liquid cooling plate to obtain flow channel grooves; S6: Brazing: The upper plate of the liquid cooling plate is brazed with the stamped lower plate of the liquid cooling plate under gas protection to obtain the liquid cooling plate.
[0028] Further, in step S1, the melting temperature is 700–750℃; in step S2, the homogenization treatment temperature is 520–590℃, and the time is 10–24 h; in step S3, the initial rolling temperature of the composite hot rolling is 400–480℃, and the thickness after rolling is 4–10 mm; in step S4, the annealing temperature is 240–320℃, the time is 1–4 h, and the thickness of the upper and lower liquid-cooled plates is 0.5–4 mm; in step S6, the brazing temperature is 590–620℃, the holding time is 3–10 min, and the protective gas is nitrogen.
[0029] To better understand the present invention, specific examples are provided below to further illustrate the content of the present invention, but the content of the present invention is not limited to the examples below.
[0030] Example 1 (1) Melting: According to the alloy ratios of the upper plate substrate 1, the upper plate inner anti-corrosion layer 2, the lower plate brazing layer 3, the lower plate inner anti-corrosion layer 4, and the lower plate substrate 5 in Table 1, the aluminum liquid is obtained by batching and melting; wherein, the melting temperature is 730℃ and the casting speed is 60 mm / min. (2) Casting: The above-mentioned aluminum liquid is processed in a converter, and then refined with Ar gas at 720℃ for 30 min. After standing for 30 min, it is degassed and filtered before casting to obtain ingots of upper plate substrate 1, upper plate inner anti-corrosion layer 2, lower plate brazing layer 3, lower plate inner anti-corrosion layer 4 and lower plate substrate 5. Then, the ingots are sawed and milled to remove 60 mm of the head and tail areas respectively, and the milling amount of each surface is 8 mm. Among them, the ingots of upper plate substrate 1 and lower plate substrate 5 need to be homogenized before sawing and milling at a temperature of 550℃ for 20 h. (3) Composite hot rolling: The above-mentioned upper plate substrate 1 and the upper plate inner anti-corrosion layer 2 ingots are placed in sequence and fixed with rivets. The above-mentioned lower plate brazing layer 3, lower plate inner anti-corrosion layer 4 and lower plate substrate 5 ingots are placed in sequence and fixed with rivets. Then, composite hot rolling is carried out separately. The initial rolling temperature is 480℃. Finally, it is rolled to 6mm to obtain upper plate hot rolling plate and lower plate hot rolling plate. (4) Cold rolling: The hot-rolled upper plate and the hot-rolled lower plate obtained above are subjected to multiple cold rolling passes and then annealed. The annealing temperature is 280℃ and the time is 3h. Finally, a liquid-cooled upper plate and a liquid-cooled lower plate with a thickness of 1 mm are obtained. The coverage rate of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate is 5%, and the coverage rate of the brazing layer 3 of the lower plate is 10%. (5) Stamping: Stamping is performed on the lower plate of the liquid cooling plate to obtain the flow channel groove; (6) Brazing: The upper plate of the above-mentioned liquid cooling plate is brazed with the stamped lower plate of the liquid cooling plate under gas protection. The protective gas is nitrogen. The brazing temperature is 600℃ and the holding time is 8min. The liquid cooling plate is finally obtained (e.g., Figure 1 ).
[0031] Table 1 Alloy composition (wt.%) in Example 1 Example 2 (1) Melting: According to the alloy ratios of the upper plate substrate 1, the upper plate inner anti-corrosion layer 2, the lower plate brazing layer 3, the lower plate inner anti-corrosion layer 4, and the lower plate substrate 5 in Table 1, the aluminum liquid is prepared and melted respectively; wherein, the melting temperature is 720℃ and the casting speed is 80 mm / min. (2) Casting: The above-mentioned aluminum liquid is processed in a converter, and then refined with Ar gas at 720℃ for 30 min. After standing for 30 min, it is degassed and filtered before casting to obtain ingots of upper plate substrate 1, upper plate inner anti-corrosion layer 2, lower plate brazing layer 3, lower plate inner anti-corrosion layer 4 and lower plate substrate 5. Then, the ingots are sawed and milled to remove 60 mm of the head and tail areas respectively, and the milling amount of each surface is 8 mm. Among them, the ingots of upper plate substrate 1 and lower plate substrate 5 need to be homogenized before sawing and milling at a temperature of 550℃ for 20 h. (3) Composite hot rolling: The above-mentioned upper plate substrate 1 and the upper plate inner anti-corrosion layer 2 ingots are placed in sequence and fixed with rivets. The above-mentioned lower plate brazing layer 3, lower plate inner anti-corrosion layer 4 and lower plate substrate 5 ingots are placed in sequence and fixed with rivets. Then, composite hot rolling is carried out separately. The initial rolling temperature is 480℃. Finally, it is rolled to 4mm to obtain the liquid-cooled upper plate and the lower plate hot-rolled plate. (4) Cold rolling: The hot-rolled upper plate and the hot-rolled lower plate obtained above are subjected to multiple cold rolling and annealing. The annealing temperature is 300℃ and the time is 3h. Finally, a liquid-cooled upper plate and a liquid-cooled lower plate with a thickness of 1.2 mm are obtained. The coverage rate of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate is 10%, and the coverage rate of the brazing layer of the lower plate is 15%.
[0032] (5) Stamping: Stamping is performed on the lower plate of the liquid cooling plate to obtain the flow channel groove; (6) Brazing: The upper plate of the above liquid cooling plate is brazed with the lower plate of the stamped liquid cooling plate under gas protection. The protective gas is nitrogen. The brazing temperature is 610℃ and the holding time is 5min. Finally, the liquid cooling plate is obtained.
[0033] Table 2 Alloy composition (wt.%) in Example 2 Example 3 Example 3 is basically the same as Example 1, except that the coverage rates of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate are different; in Example 3, the coverage rate of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate is 10%.
[0034] Example 4 Example 4 is basically the same as Example 1, except that the coverage rates of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate are different; in Example 4, the coverage rate of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate is 15%.
[0035] Example 5 Example 5 is basically the same as Example 2, except that the coverage rates of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate are different; in Example 5, the coverage rate of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate is 5%.
[0036] Example 6 Example 6 is basically the same as Example 2, except that the coverage rates of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate are different; in Example 6, the coverage rate of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate is 15%.
[0037] Example 7 Example 7 is basically the same as Example 2, except that the 7xxx series modified aluminum alloy composition of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate are different; in Example 7, the alloy composition of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate is shown in Table 3.
[0038] Table 3. Alloy composition (wt.%) of the inner anti-corrosion layer of the upper and lower plates in Example 7 Example 8 Example 8 is basically the same as Example 1, except that the 1xxx series modified aluminum alloy composition of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate are different; in Example 8, the alloy composition of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate is shown in Table 4.
[0039] Table 4. Alloy composition of the inner anti-corrosion layer of the upper and lower plates in Example 8 (wt.%) Comparative Example 1 (1) Melting: Aluminum liquid is obtained by batching and melting according to the alloy ratios of the upper plate substrate, the lower plate brazing layer and the lower plate substrate in Table 5; wherein, the melting temperature is 730℃ and the casting speed is 60 mm / min. (2) Casting: The above-mentioned aluminum liquid is processed in a converter, and then refined with Ar gas at 720℃ for 30 minutes. After standing for 30 minutes, it is degassed and filtered before casting to obtain the upper plate substrate, the lower plate brazing layer and the lower plate substrate ingots. After casting, the above ingots need to be sawed and milled. The head and tail areas of 60mm are sawed off respectively, and the milling amount of each surface is 8mm. Among them, the upper plate substrate and the lower plate substrate ingots need to be homogenized before sawing and milling at a temperature of 550℃ for 20 hours. (3) Composite hot rolling: The ingot of the upper plate substrate is hot rolled, and the ingot of the lower plate brazing layer and the lower plate substrate are placed in sequence and fixed with rivets before composite hot rolling. The initial rolling temperature is 480℃, and the final rolling is 6mm to obtain the upper plate hot rolled plate and the lower plate hot rolled plate. (4) Cold rolling: The hot-rolled upper plate and the hot-rolled lower plate obtained above are subjected to multiple cold rolling passes and then annealed. The annealing temperature is 280℃ and the time is 3h, and finally a liquid-cooled upper plate and a liquid-cooled lower plate with a thickness of 1 mm are obtained. The brazing layer of the lower plate has a coverage rate of 10%. (5) Stamping: Stamping is performed on the lower plate of the liquid cooling plate to obtain the flow channel groove; (6) Brazing: The upper plate of the above liquid cooling plate is brazed with the lower plate of the stamped liquid cooling plate under gas protection. The protective gas is nitrogen. The brazing temperature is 600℃ and the holding time is 8min. Finally, the liquid cooling plate is obtained.
[0040] Table 5. Alloy composition (wt.%) in Comparative Example 1 Comparative Example 2 (1) Melting: Aluminum liquid is obtained by batching and melting according to the alloy ratios of the upper plate substrate, the lower plate brazing layer and the lower plate substrate in Table 6; wherein, the melting temperature is 720℃ and the casting speed is 80 mm / min. (2) Casting: The above-mentioned aluminum liquid is processed in a converter, and then refined with Ar gas at 720℃ for 30 minutes. After standing for 30 minutes, it is degassed and filtered before casting to obtain the upper plate substrate, the lower plate brazing layer and the lower plate substrate ingots. After casting, the above ingots need to be sawed and milled. The head and tail areas of 60mm are sawed off respectively, and the milling amount of each surface is 8mm. Among them, the upper plate substrate and the lower plate substrate ingots need to be homogenized before sawing and milling at a temperature of 520℃ for 24 hours. (3) Composite hot rolling: The ingot of the upper plate substrate is hot rolled, and the ingot of the lower plate brazing layer and the lower plate substrate are placed in sequence and fixed with rivets before composite hot rolling. The initial rolling temperature is 460℃, and the final rolling is 4mm to obtain the upper plate hot rolled plate and the lower plate hot rolled plate. (4) Cold rolling: The hot-rolled upper plate and the hot-rolled lower plate obtained above are subjected to multiple cold rolling passes and then annealed. The annealing temperature is 300℃ and the time is 3h, and finally a liquid-cooled upper plate and a liquid-cooled lower plate with a thickness of 1.2mm are obtained. The brazing layer of the lower plate has a coverage rate of 10%. (5) Stamping: Stamping is performed on the lower plate of the liquid cooling plate to obtain the flow channel groove; (6) Brazing: The upper plate of the above liquid cooling plate and the lower plate of the stamped liquid cooling plate are brazed under gas protection. The protective gas is nitrogen. The brazing temperature is 610℃ and the holding time is 5min. Finally, the liquid cooling plate is obtained.
[0041] Table 6 Alloy composition (wt.%) in Comparative Example 2 Comparative Example 3 Comparative Example 3 is basically the same as Example 1, except that the coverage rates of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate are different; in Comparative Example 3, the coverage rates of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate are 1%.
[0042] Comparative Example 4 Comparative Example 4 is basically the same as Example 2, except that the coverage rates of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate are different; in Comparative Example 4, the coverage rate of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate is 18%.
[0043] Comparative Example 5 Comparative Example 5 is basically the same as Example 1, except that the 1xxx series modified alloy composition of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate is different; in Comparative Example 5, the 1xxx series modified alloy composition of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate is shown in Table 7.
[0044] Table 7. Alloy composition (wt.%) of the inner anti-corrosion layer in Comparative Example 5 Comparative Example 6 Comparative Example 6 is basically the same as Example 2, except that the 7xxx series modified alloy composition of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate are different; in Comparative Example 6, the alloy composition of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate in step (1) is shown in Table 8.
[0045] Table 8. Alloy composition (wt.%) of the inner anti-corrosion layer in Comparative Example 6 Comparative Example 7 Comparative Example 7 is basically the same as Example 1, except that the 1xxx series modified alloy composition of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate are different; in Comparative Example 7, the alloy composition of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate is shown in Table 9.
[0046] Table 9. Alloy composition (wt.%) of the inner anti-corrosion layer in Comparative Example 7 Comparative Example 8 Comparative Example 8 is basically the same as Example 2, except that the 7xxx series modified alloy composition of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate are different; in Comparative Example 8, the alloy composition of the inner anti-corrosion layer 2 of the upper plate and the inner anti-corrosion layer 4 of the lower plate is shown in Table 10.
[0047] Table 10. Alloy composition (wt.%) of the inner anti-corrosion layer in Comparative Example 8 Test case According to GB / T 228.1-2021 Part 1: Room temperature test method, the mechanical properties of the upper and lower liquid cooling plates prepared in each embodiment and comparative example were tested, and the results are shown in Table 11.
[0048] According to GB / T29743.2 Part 2: Coolants for Electric Vehicles, static corrosion performance tests were conducted on the liquid-cooled plates prepared in each embodiment and comparative example. After the tests, the maximum corrosion depth of the liquid-cooled plates was observed, and the results are shown in Table 12. Figure 3 .
[0049] Table 11 Mechanical property results of the examples and comparative examples Table 12 Static corrosion results of the examples and comparative examples Comparative experimental results show that Comparative Examples 1 and 2 without anti-corrosion layers exhibit corrosion depths as high as 514–537 μm in low-conductivity coolants (GB / T 29743.2), indicating severe electrochemical corrosion. However, in Examples 1 and 2, using 1xxx and 7xxx series modified aluminum alloys as inner anti-corrosion layers respectively, the corrosion depths decreased sharply to 33.7 μm and 45.7 μm, a reduction of over 90%. This demonstrates that composite anti-corrosion layers of 1xxx or 7xxx series modified aluminum alloys on the inner side of the liquid cooling plate can significantly improve its corrosion resistance in low-conductivity coolant environments.
[0050] The coating ratio has a significant impact on corrosion resistance. In the 1xxx series anti-corrosion coating scheme, when the coating ratio is less than 5% (Comparative Example 3, coating ratio 1%), the corrosion depth is as high as 282.6 μm, indicating that when the anti-corrosion layer is too thin, it cannot effectively cover and protect the substrate, and the corrosive medium can easily penetrate the anti-corrosion layer and reach the substrate. When the coating ratio is in the range of 5% to 15% (Examples 1, 3, 4), the corrosion depth is stable at 33.7 to 35.4 μm. In the 7xxx series anti-corrosion coating scheme, when the coating ratio is in the range of 5% to 15% (Examples 2, 5, 6), the corrosion depth is stable at 44.8 to 47.2 μm.
[0051] As the coverage ratio increases, the tensile strength of the 1xxx series anti-corrosion coating decreases from 131.0 MPa (5%) to 116.4 MPa (15%), and the yield strength decreases from 48.5 MPa to 45.8 MPa, showing a downward trend. This is because the strength of the 1xxx series anti-corrosion coating itself is lower than that of the 3003 substrate. The higher the coverage ratio, the higher the proportion of low-strength anti-corrosion coating, resulting in a decrease in overall strength. In the 7xxx series, the tensile strength decreases from 163.6 MPa (5%) to 158.4 MPa (15%), and the yield strength decreases from 63 MPa to 61.3 MPa, showing a downward trend. When the coverage ratio increases to 18% (Comparative Example 4), the tensile strength decreases to 153.2 MPa, and the yield strength decreases to 58.2 MPa, showing a significant downward trend.
[0052] Zr significantly improves the corrosion resistance and mechanical properties of anti-corrosion coatings. In the 1xxx series, the addition of Zr reduced the corrosion depth from 52.4 μm to 33.7 μm (a decrease of 35.7%), and increased the tensile strength from 128.0 MPa to 131.0 MPa. In the 7xxx series, the addition of Zr reduced the corrosion depth from 64.3 μm to 45.7 μm (a decrease of 28.9%), and increased the tensile strength from 156.5 MPa to 161.6 MPa. This indicates that Zr produces a synergistic strengthening effect in both 1xxx and 7xxx series anti-corrosion coatings, refining the grain size and increasing the density of the oxide film, thereby improving corrosion resistance, and also improving mechanical properties through a grain refinement strengthening mechanism.
[0053] As impurity elements in aluminum alloys, the increased content of Si and Fe significantly reduces corrosion resistance. In the 1xxx series schemes, when the Si and Fe contents increased from 0.1% (Example 1) to 0.5% (Example 8), the corrosion depth increased from 33.7 μm to 39.8 μm (an increase of 18.1%); when increased to 0.8% (Comparative Example 5), the corrosion depth increased sharply to 92.6 μm (an increase of 174.8%). This is because Si and Fe form second phases such as FeAl3 and AlFeSi, which form microgalvanic corrosion with the matrix, promoting the initiation and propagation of pitting corrosion.
[0054] In the 7xxx series anti-corrosion coating scheme, the Zn content has a significant impact on corrosion resistance. When the Zn content increases from 1.2% (Example 2) to 2.0% (Example 7), the corrosion depth decreases from 45.7 μm to 40.2 μm (a decrease of 12.0%), indicating that appropriately increasing the Zn content can enhance the sacrificial anode protection effect. However, when the Zn content exceeds 2.0% and reaches 2.5% (Comparative Example 6), the corrosion depth rises sharply to 123.9 μm (an increase of 170.9%). This is because when the Zn content is too high, the corrosion rate of the anti-corrosion coating itself is too fast, and overburning is prone to occur during brazing, leading to microstructural deterioration.
[0055] Comparing the mechanical property data of Examples 1-8 and Comparative Examples 1-2, it can be seen that the mechanical properties of the liquid cooling plate after the composite anti-corrosion layer are basically the same as or slightly different from those without the anti-corrosion layer. For example, the tensile strength of Example 1 (1xxx series, 5% coating rate) is 131.0 MPa, while that of Comparative Example 1 (without anti-corrosion layer) is 133.3 MPa, with minimal difference. The tensile strength of Example 2 (7xxx series, 10% coating rate) is 161.6 MPa, while that of Comparative Example 2 (without anti-corrosion layer) is 165.4 MPa, with similarly minor differences. This indicates that the anti-corrosion layer of the present invention, within the coating rate range of 5% to 15%, has little impact on the overall mechanical properties of the liquid cooling plate, and can significantly improve corrosion resistance while ensuring mechanical properties, achieving a balance between mechanical properties and corrosion resistance.
[0056] Both 1xxx and 7xxx series anti-corrosion coatings can effectively improve the corrosion resistance of liquid cooling plates in low-conductivity coolants, but their anti-corrosion mechanisms differ. The 1xxx series relies on the chemical inertness of the pure aluminum substrate and the dense oxide film to achieve "barrier protection," resulting in almost no pitting corrosion. The 7xxx series relies on Zn to lower the potential, allowing the anti-corrosion layer to act as a "sacrificial anode" for preferential and uniform corrosion, protecting the substrate. In terms of corrosion depth data, the 1xxx series (33.7–39.8 μm) is slightly better than the 7xxx series (40.2–47.2 μm), but the 7xxx series has higher mechanical strength (tensile strength up to 166.5 MPa), and its sacrificial anode protection mechanism still provides protection even when the anti-corrosion layer is partially damaged, offering higher safety.
[0057] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A liquid cooling plate for a power battery, characterized in that, The system includes an upper liquid cooling plate and a lower liquid cooling plate. The upper liquid cooling plate includes an upper substrate (1) and an inner anti-corrosion layer (2). The lower liquid cooling plate includes a lower brazing layer (3), an inner anti-corrosion layer (4), and a lower substrate (5). The upper substrate (1) and the lower substrate (5) are made of 3003 aluminum alloy or 3003 modified aluminum alloy. The brazing layer (3) of the lower plate is made of 4045 aluminum alloy or 4343 aluminum alloy. The inner anti-corrosion layer (2) of the upper plate and the inner anti-corrosion layer (4) of the lower plate are made of 1xxx series modified aluminum alloy or 7xxx series modified aluminum alloy. The mass percentage composition of the 1xxx series modified aluminum alloy is: Si≤0.5w. The 7xxx series modified aluminum alloy has the following mass percentage composition: Si≤0.7wt.%, Fe≤0.8wt.%, Cu≤0.3wt.%, Mn≤0.3wt.%, Mg≤0.3wt.%, Zn≤0.1wt.%, Ti:0.05~0.2wt.%, Zr:0.05~0.2wt.%, and the balance Al; 2. The power battery liquid cooling plate according to claim 1, characterized in that, The 3003 aluminum alloy has the following mass percentage composition: Si ≤ 0.6 wt.%, Fe ≤ 0.7 wt.%, Cu: 0.05~0.20 wt.%, Mn: 1.0~1.5 wt.%, Zn ≤ 0.1 wt.%, and the balance Al; the 3003 modified aluminum alloy has the following mass percentage composition: Si: 0.1~1.0 wt.%, Fe: 0.1~1.0 wt.%, Cu: 0.2~1.2 wt.%, Mn: 1.0~1.8 wt.%, Mg ≤ 0.05 wt.%, Zn ≤ 0.1 wt.%, Ti: 0.05~0.30 wt.%, and the balance Al.
3. The power battery liquid cooling plate according to claim 1, characterized in that, The 4045 aluminum alloy has the following mass percentage composition: Si: 9-11 wt.%, Fe≤0.8 wt.%, Cu≤0.30 wt.%, Mn≤0.05 wt.%, Mg≤0.05 wt.%, Zn≤0.1 wt.%, Ti≤0.2 wt.%, and the balance Al; the 4343 aluminum alloy has the following mass percentage composition: Si: 6.8-8.2 wt.%, Fe≤0.8 wt.%, Cu≤0.25 wt.%, Mn≤0.1 wt.%, Zn≤0.2 wt.%, and the balance Al.
4. The power battery liquid cooling plate according to claim 1, characterized in that, The coverage rate of the brazing layer (3) on the lower plate is 5% to 15%.
5. The power battery liquid cooling plate according to claim 1, characterized in that, The coverage rate of the inner anti-corrosion layer (2) of the upper plate and the inner anti-corrosion layer (4) of the lower plate is 5% to 15%.
6. A method for preparing the liquid-cooled plate according to any one of claims 1-5, characterized in that, Includes the following steps: S1: Melting: Melting is carried out according to the alloy composition ratios of the upper plate substrate (1) and the upper plate inner anti-corrosion layer (2), the lower plate brazing layer (3), the lower plate inner anti-corrosion layer (4) and the lower plate substrate (5) to obtain aluminum liquid; S2: Casting: The aluminum liquid is cast after being passed through a converter, refined, settled, degassed and filtered to obtain ingots. Then, the ingots are sawed and milled to obtain upper plate substrate (1), upper plate inner anti-corrosion layer (2) ingots, lower plate brazing layer (3), lower plate inner anti-corrosion layer (4) and lower plate substrate (5) ingots; wherein, the upper plate substrate (1) and lower plate substrate (5) ingots are homogenized before sawing and milling. S3: Composite hot rolling: After stacking and fixing the upper plate substrate (1) and the inner anti-corrosion layer (2) of the upper plate, composite hot rolling is performed. After stacking and fixing the lower plate brazing layer (3), the inner anti-corrosion layer (4) of the lower plate and the lower plate substrate (5), composite hot rolling is performed to obtain the upper plate hot-rolled plate and the lower plate hot-rolled plate. S4: Cold rolling: The upper hot-rolled plate and the lower hot-rolled plate are cold-rolled and then annealed to obtain the upper liquid-cooled plate and the lower liquid-cooled plate. S5: Stamping: Stamping the lower plate of the liquid cooling plate to obtain flow channel grooves; S6: Brazing: The upper plate of the liquid cooling plate is brazed with the stamped lower plate of the liquid cooling plate under gas protection to obtain the liquid cooling plate.
7. The method according to claim 6, characterized in that, In step S1, the melting temperature is 700–750℃; in step S2, the homogenization treatment temperature is 520–590℃, and the time is 10–24 h; in step S3, the initial rolling temperature of the composite hot rolling is 400–480℃, and the thickness after rolling is 4–10 mm; in step S4, the annealing temperature is 240–320℃, the time is 1–4 h, and the thickness of the upper and lower liquid-cooled plates is 0.5–4 mm; in step S6, the brazing temperature is 590–620℃, the holding time is 3–10 min, and the protective gas is nitrogen.